Regulation of Biofilm Exopolysaccharide Production by Cyclic Di-Guanosine Monophosphate - Poulin, Myles B.; Kuperman, Laura L. (Frontiers in Microbiology, 2021)
Many bacterial species in nature possess the ability to transition into a sessile lifestyle and aggregate into cohesive colonies, known as biofilms. Within a biofilm, bacterial cells are encapsulated within an extracellular polymeric substance (EPS) comprised of polysaccharides, proteins, nucleic acids, lipids, and other small molecules. The transition from planktonic growth to the biofilm lifecycle provides numerous benefits to bacteria, such as facilitating adherence to abiotic surfaces, evasion of a host immune system, and resistance to common antibiotics. As a result, biofilm-forming bacteria contribute to 65% of infections in humans, and substantially increase the energy and time required for treatment and recovery. Several biofilm specific exopolysaccharides, including cellulose, alginate, Pel polysaccharide and poly-N-acetylglucosamine (PNAG), have been shown to play an important role in bacterial biofilm formation and their production is strongly correlated with pathogenicity and virulence. In many bacteria the biosynthetic machineries required for assembly of these exopolysaccharides are regulated by common signaling molecules, with the second messenger cyclic di-guanosine monophosphate (c-di-GMP) playing an especially important role in the post-translational activation of exopolysaccharide biosynthesis. Research on treatments of antibiotic-resistant and biofilm-forming bacteria through direct targeting of c-di-GMP signaling has shown promise, including peptide-based treatments that sequester intracellular c-di-GMP. In this review, we will examine the direct role c-di-GMP plays in the biosynthesis and export of biofilm exopolysaccharides with a focus on the mechanism of post-translational activation of these pathways, as well as describe novel approaches to inhibit biofilm formation through direct targeting of c-di-GMP.